4H Leukodystrophy: Lessons from 3T Imaging - Cayami, Ferdy K.; Bugiani, Marianna; Pouwels, Petra J.W.; Bernard, Geneviève; van der Knaap, Marjo S.; Wolf, Nicole I. (Neuropediatrics, 2018)
4H leukodystrophy is characterized by hypomyelination, hypodontia, and hypogonadotropic hypogonadism. With its variability in clinical symptoms, application of pattern recognition to identify specific magnetic resonance imaging (MRI) features proved useful for the diagnosis. We collected 3T MR imaging data of 12 patients with mutations in POLR3A (n = 8), POLR3B (n = 3), and POLR1C (n = 1), all obtained at the same scanner. We assessed these images and compared them with previously obtained 1.5T images in 8 patients. Novel MRI findings were myelin islets, closed eye sign, and a cyst-like lesion in the splenium. Myelin islets were variable numbers of small T1 hyperintense and T2 hypointense dots, mostly in the frontal and parietal white matter, and present in all patients. This interpretation was supported with perivascular staining of myelin protein in the hypomyelinated white matter of a deceased 4H patient. All patients had better myelination of the medial lemniscus with a relatively hypointense signal of this structure on axial T2-weighted (T2W) images (“closed eye sign”). Five patients had a small cyst-like lesion in the splenium. In 10 patients with sagittal T2W images, we also found spinal cord hypomyelination. In conclusion, imaging at 3T identified additional features in 4H leukodystrophy, aiding the MRI diagnosis of this entity.
Keywords: 4H leukodystrophy; MRI; 3T